A study on the policy and model of large-scale effective training to rural compulsory education teachers: A case study of Beijing "Green-Planting Action" - Xiuzhi Yong (Adult Education Research Conference, 2014)
Using Beijing "green-planting action" as a case study, the author exams and analyzes the policy and the implementation of a ten-year long, large-scale training for rural compulsory education teachers in the suburban districts and counties of Beijing. In this presentation, the author frist summarizes the large-scale training rules and characteristics, then examines the effectiveness of the model for large-scale training of rural teachers. It is hoped that the study provides some strategies to improve the quality of teachers’ training, puts forth a scientific basis for decision making and reasonable policy recommendations. It conlceds with a review of the balanced development of compulsory education.